2011
DOI: 10.3747/pdi.2010.00110
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Conscious Sedation, An Alternative to General Anesthesia for Laparoscopic Peritoneal Dialysis Catheter Implantation: A Randomized Trial Comparing Intravenous and Subcutaneous Ketamine

Abstract: Dissociative conscious sedation is an acceptable alternative to general anesthesia in laparoscopic implantation of the PD catheter. Ketamine by the SC route is as effective as, but safer than, IV ketamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Psychomimetic side effects have not been reported after rectal administration, which is known to result in low plasma levels (23). As shown in this study a subcutaneous injection might therefore provide analgesia without hallucinations or other psychomimetic effects (26). This study demonstrated no significant hemodynamic changes (heart rate and blood pressure) with ketamine administration.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Psychomimetic side effects have not been reported after rectal administration, which is known to result in low plasma levels (23). As shown in this study a subcutaneous injection might therefore provide analgesia without hallucinations or other psychomimetic effects (26). This study demonstrated no significant hemodynamic changes (heart rate and blood pressure) with ketamine administration.…”
Section: Discussionmentioning
confidence: 55%
“…at 60 and 360 minutes after the operation) more than IV ketamine injection(0.5 mg/kg). This effect is probably because of gradual absorption of ketamine in subcutaneous administration (26). Several advantages of S.C ketamine such as lower incidence of psychomimetic side effects have been documented by keeping the plasma concentration at 150ng/ ml and even lower (22).…”
Section: Discussionmentioning
confidence: 99%
“…There was more co-morbidity in the LA group, a result of confounding by indication, since it was elected to use LA because of the higher risk for GA [9].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CO 2 is rapidly absorbed across the peritoneal membrane and may contribute to significant metabolic acidosis and cardiac arrhythmias [14,15], disturbances that are not well tolerated by high-risk renal failure patients [10]. Alternatively, N 2 O is an inert gas and better tolerated as an insufflation agent [16], because it produces neither peritoneal irritation nor the metabolic effects, offering a plausible explanation for absence of pain and thus enabling laparoscopy with the patient under local anesthesia [9,12]. Combined with the mild conscious sedation which is appropriate to alleviate undue fear and anxiety, the procedure can be tolerated well without GA [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation